Chapter: 'Introduction' from book: Public Brainpower: Civil Society and Natural Resource Management - Indra Overland (Palgrave Macmillan, 2017)
This introductory chapter establishes the analytical framework for the edited volume. The literature on the resource curse and institutions is briefly discussed, along with the work on civil society and the public sphere by Almond and Verba, Dahl, Habermas and Putnam. Drawing on these classics, the theoretical concept of 'public brainpower' is formulated. The main pillar of public brainpower is polycentricity, or the coexistence of many different public actors freely expressing their thoughts: individual citizens, political parties, trade unions, charities, companies, research institutes, religious institutions, mass media and government institutions. The more polycentric a society is, the greater is its brainpower: its memory becomes more comprehensive and multifaceted, different actors can perform quality control of each other's ideas and arguments, and it is more difficult to repress challenging views. Above all, a polycentric society has a broader base for creativity. The greater the public brainpower of a society, the better its management of natural resources. Finally, the book's 18 case studies of oil- and gas-producing countries are briefly presented, along with the methodology and definitions of key terminology used throughout the volume.